INTEGRATION OF CALLIGRAPHY IN READING AND WRITING THE QURAN: ANALYSIS OF QURAN WRITING SKILLS AMONG ELEMENTARY SCHOOL STUDENTS - Iffah Muyassaroh; Siti Khamim; Muhammad Nurul Mubin (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
This study aims to determine the effectiveness and application of the calligraphy method in the learning of reading and writing the Quran (QRW) at SDN Malangrejo Sleman, with the aim of enhancing students' abilities in Quranic learning. This research employs a qualitative descriptive analysis method, with data collected through observation, interviews, and documentation. The results show that teaching Quran reading and writing through calligraphy can foster and develop students' creativity, namely teaching students to appreciate the art of calligraphy. Therefore, the calligraphy method in QRW learning at SDN Malangrejo Sleman is effective and innovative in teaching Quran reading and writing. The urgency of implementing this approach includes: understanding, reading, and writing the Quran correctly, preventing students from boredom in learning to read and write the Quran, and training student autonomy. This research is expected to have significant potential to be adopted by schools, and other Islamic education teachers, in order to improve the quality of learning Quran reading and writing in general. As a result of this study, teachers and educational institutions can consider the calligraphy method as an alternative approach in learning to read and write the Quran because it has the potential to increase creativity and students' interest.